Spontaneous scapular region hematoma extending upto anterior chest wall in a patient of chronic myeloid leukaemia: an unusual site presentation - Gopal, Vaibhav Raj; Srivastava, Akash; Yadav, Neha; Singh, Vineet Kumar (International Surgery Journal, 2022)
Spontaneous haemorrhage and thrombosis should always raise the suspicion of CML as one of the differential as it is associated with qualitative platelet dysfunction. We here report a rare case of CML with spontaneous hematoma at an unusual site. A 26 years male presented with complaints of sudden onset non traumatic spontaneous swelling over the left scapular region and progressively extending up-to the left anterior chest wall which was associated with dull aching moderate intensity pain. Swelling was warm, soft in consistency and tender. He also had hepato-splenomegaly. General blood picture showed marked leucocytosis with myeloid hyperplasia. CT scan thorax reported a large hypodense lesion in the scapular and anterior chest wall region which on diagnostic aspiration revealed blood thereby confirming the diagnosis of spontaneous hematoma with CML. Imatinib therapy was started and hematoma was managed conservatively with antibiotics. The swelling resolved spontaneously without any surgical intervention.